Occupational therapy in pulmonary rehabilitation programs: A scoping review. (August 2022) - Finch, Lian; Frankel, Daniel; Gallant, Brooklyn; Landa, Chris; Snyder, Natalie; Wilson, Ria; Packham, Tara; Brooks, Dina; Oliveira, Ana
Abstract: Pulmonary rehabilitation (PR) is a multidisciplinary intervention forming the cornerstone of chronic respiratory disease management, improving individuals' exercise capacities and abilities to complete activities of daily living (ADLs). Although the occupational therapy (OT) scope of practice focuses on similar outcomes as PR, the tasks/roles and benefit of including OT in PR has not been reviewed. This scoping review synthesized the i) tasks/roles, ii) recommendations of guidelines, iii) prevalence and iv) effects of OT as part of PR programs. Searching of four databases (MEDLINE, EMBASE, CINAHL and Cochrane), OT association websites, and hand searching was performed, and 51 records were included. The OT tasks/roles most reported include teaching energy conservation techniques (n = 23), addressing ADLs (n = 17), and assisting with breathlessness management (n = 10). Using the Canadian Model of Occupational Performance and Engagement these tasks/roles were grouped into person (n = 16 unique tasks/roles), occupation (n = 6 tasks/roles), environment (n = 5 tasks/roles), and other (n = 3 tasks/roles) domains and were endorsed by two available practice guidelines addressing OT in PR programs. From 13 PR surveys across four continents, 17–92% of PR programs included OT. Inclusion of OT in PR resulted in positive effects on ADLs, pulmonary function, dyspnea, quality of life, and mortality. Although an increasing number of PR programs include occupational therapists in their multidisciplinary teams, there is a paucity of original studies and guidelines reporting on the tasks/roles and benefits of OT in PR. Further research is needed to clearly define the tasks/roles of OT in multidisciplinary PR teams and contributions to enhancing patient outcomes. Highlights: Education of energy conservation, ADLs and breathing techniques are common OT tasks/roles. The presence of OT in PR varies widely within and among surveys of PR programs. There is a paucity of up-to-date recommendations for the inclusion of OT in PR. Including OT as part of PR appears to have a positive effect on patient outcomes.